Efficacy and safety of switching to dolutegravir plus lamivudine versus continuing triple antiretroviral therapy in virologically suppressed adults with HIV at 48 weeks (DOLAM): a randomised non-inferiority trial. Issue 8 (August 2021) - Rojas, Jhon; de Lazzari, Elisa; Negredo, Eugenia; Domingo, Pere; Tiraboschi, Juan; Ribera, Esteve; Abdulghani, Nadia; Puig, Jordi; Mateo, Maria G; Podzamczer, Daniel; Gutierrez, Maria M; Paredes, Roger; et al.
Summary: Background: Simplified antiretroviral therapy (ART) regimens are desirable for people with HIV. We investigated the efficacy and safety of switching from triple ART to dual dolutegravir plus lamivudine therapy. Methods: DOLAM is a phase 4, randomised, open-label, non-inferiority trial, done at six HIV clinics in Catalonia, Spain. Adults with HIV-1 receiving a triple ART regimen, aged 18 years or older, with virological suppression, a CD4 nadir of at least 200 cells per μL, who were HBsAg-negative, and without previous viral failure or resistance mutations to study drugs were eligible. Participants underwent computer-generated randomisation, stratified by the class of the third drug, and were assigned (1:1) to switch to oral dolutegravir 50 mg and lamivudine 300 mg once daily or to continue triple ART for 48 weeks. The primary endpoint was the proportion of people with an HIV RNA value of at least 50 copies per mL at week 48 (US Food and Drug Administration snapshot algorithm, 8% non-inferiority margin). Both the primary and safety outcomes were evaluated in the intention-to-treat exposed population. The study is completed and was registered with EudraCT 201500027435. Findings: Between July 7, 2015, and Oct 31, 2018, 265 participants were randomly assigned to switch to dolutegravir plus lamivudine (n=131) or to maintain triple ART (n=134) and all received at least one dose. Nine (7%) participants in the dual therapy group and ten (7%) in the triple therapy group were excluded before 48 weeks, mostly due to treatment discontinuations or virological failure. Participants were predominantly male (116 [87%] of 134 in the triple ART group and 111 [85%] of 131 in the dolutegravir plus lamivudine group). The difference in the proportion of participants with HIV RNA values of at least 50 copies per mL at 48 weeks between the dual therapy group (three [2%] of 131) and triple therapy group (two [1%] of 134) was 0·8 percentage points (95% CI –3·3 to 5·2), showing non-inferiority of dolutegravir plus lamivudine dual therapy compared with triple ART. 73 (56%) of 131 participants allocated to dual therapy had 150 adverse effects, compared with 78 (58%) of 134 participants allocated to triple therapy who also had 150 adverse events (p=0·68). Drug discontinuation due to adverse effects occurred in four people in the triple therapy group and three people in the dual therapy group. Interpretation: Our findings show the efficacy and safety of dolutegravir plus lamivudine as a simplified therapy switch option for selected people with HIV with virological suppression on triple ART. Funding: Instituto de Salud Carlos III, Red de Investigación en Sida, and ViiV Healthcare.